Ureter wounds - Castiglioni, Juan C.; Cuneo, Roberto; Bergalli, Luis E.; Soto, Juan P.; Saccone, Rodolfo (Cirugía del Uruguay, 1974)
Case material comprises 5 ureter wounds caused by bullets. An infrequent lesion, its pathology is discussed with stress on pathogeny of deferred lesions caused by high-speed bullets. An early diagnosis is both important and difficult and excretion urography is useful as an urgency test. Surgical treatment of ureter wounds, with poor functional prognosis, is outlined in this paper.